2010
DOI: 10.1021/jp911202d
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Study of the Dispersion of SWNTs in Organic Solvents

Abstract: Dispersions of as-produced HiPco single-walled carbon nanotubes (SWNTs) in a series of organic solvents were prepared by dilution with the aid of tip sonication. Mild centrifugation (~ 945 g) was carried out to remove large bundles. Atomic force microscopy (AFM) studies revealed that the bundle size decreased as the dispersion was diluted. By measuring the UV-vis-NIR absorption before and after centrifugation as a function of the concentration, the dispersion limit of SWNTs in each solvent can be determined. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 18 publications
(66 reference statements)
0
76
0
Order By: Relevance
“…These percolation thresholds correlate with their low dispersion limits of 2.3 × 10 −3 wt% and 5.4 × 10 −4 wt%, respectively. 35 A low dispersion limit means that MWCNTs aggregate at low wt%, which decreases the aspect ratio of the particles and results in a high percolation threshold. 36 In the MWCNT-ILs mixtures ( Figure 1c, 1d and 1e), the percolation state is reached below 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…These percolation thresholds correlate with their low dispersion limits of 2.3 × 10 −3 wt% and 5.4 × 10 −4 wt%, respectively. 35 A low dispersion limit means that MWCNTs aggregate at low wt%, which decreases the aspect ratio of the particles and results in a high percolation threshold. 36 In the MWCNT-ILs mixtures ( Figure 1c, 1d and 1e), the percolation state is reached below 1 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…In the example of TCB, the aggregation fraction decreases with decreasing concentration until it reaches a minimum of ~ 0.1 below the dispersion limit. A complete study of the variation of dispersion limit with solvent has recently been reported 13 . AFM studies have confirmed that the reduction of the aggregation fraction is due to exfoliation of the bundles with decreasing concentration until the bundles are maximally dispersed.…”
Section: Methodsmentioning
confidence: 99%
“…However, the dispersion limit of SWNTs in TCB is only ~ 0.005 mg/ml, but the aggregation fraction below D L is found to be 0.1. AFM has demonstrated that a high aggregation fraction is due to only partial debundling of SWNTs aggregates during the sonication 13 . The dispersion limit and aggregation fraction of SWNTs below D L in each solvent are listed in Table 2, together with some of the physical parameters of the solvents, including molecular weight, viscosity, vapour pressure, density and surface tension.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, chlorinated aromatic solvents, such as mono-chlorobenzene, ortho-dichlorobenzene (ODCB), meta-dichlorobenzene and 1,2,4-trichlorobenzene, have been demonstrated to be efficient at dispersing SWCNTs [69,70]. However, it has been found that phenyl rings within solvent molecules are not the dominant factor in obtaining stable SWCNTs dispersions [71]. This conclusion is reasonably proved by poor dispersibility of SWCNTs in toluene [67].…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%
“…The dispersion quality of CNTs in solvents is also affected by the nanotube concentration and processing techniques as well as the physical parameters of as-produced CNTs [68,69,71]. However, "stable suspensions" of SWCNTs in the best organic solvents (DMF and NMP) still aggregate on a time-scale of days, even minutes, in the absence of any external agents [64].…”
Section: Carbon Nanotubes In Imidazolium Ionic Liquidsmentioning
confidence: 99%